(untitled) - Konecny, Vladimir (Doprava a spoje, 2007)
The paper deals with income elasticity of demand for passenger transport in Slovakia. Article includes both points of view - mass passenger transport (railway and bus) and individual motoring in relation to the income elasticity of demand for passenger transport. The analysis of income elasticity has based on social, economy and transportation statistical data processing and calculation.